Hydrophobically Assisted Separation-Friendly Mitsunobu Reaction - Guo, Jian; Lu, Yu-Jiao; Zhang, Li; Ye, Xin-Shan (Synlett, 2012)
A separation-friendly Mitsunobu reaction using hydrophobic-tagged acids is reported. Commercially available or simply prepared and recyclable hydrophobic-tagged acids can react with various alcohols to afford the target products in high yield with easy purification based on C-18 silica solid-phase extraction or normal silica gel filtration.
Keywords: Mitsunobu reaction; esterification; hydrophobic tag; solid-phase extraction; inversion of configuration